Rapid synthesis and consolidation of a nanostructured 3Ti-Al2O3 composite by HFIHS for biomedical application - Kwak, Bong-Won; Yoon, Jin-Kook; Shon, In-Jin (세라믹공정연구센터, 2016)
Nanopowders of TiO and Al were fabricated using high energy ball milling. Dense nanostuctured 3Ti-Al2O3 composite was simultaneously synthesized and consolidated by high frequency induction heated combustion synthesis method within 2 min in one step from mechanically activated powders of 3 TiO and 2 Al. Highly dense 3Ti-Al2O3 with relative density of up to 99.5% was produced under simultaneous application of a 80 MPa pressure and the induced current. The average hardness and fracture toughness values of the composite were 1445 kg/mm(2) and 7.2MPa . m(1/2), respectively.